Factors affecting teacher performance - Nita Kanya; Aryo Bima Fathoni; Zulmi Ramdani (International Journal of Evaluation and Research in Education (IJERE), 2021)
This study aimed to see whether there is an influence of school principal leadership, organizational culture, and teacher competence on teacher performance. Another aim was to see how much influence these factors have on teacher performance either partially or simultaneously. The research used a quantitative approach with survey methods. Analysis of the data used was multiple regression. Participants involved in the study were 385 teachers in Bandung high school by using proportional stratified random sampling. The results of the study showed that there was a significant influence on the school principal leadership variables, organizational culture, and teacher competence on teacher performance. Statistically the amount of contribution from all independent variables was 68.12%, so the remaining 32.88% was determined by other variables not measured in the study. This research was also useful to find out the factors that can improve teacher performance, so that it is expected to be a theoretical or practical consideration in schools in order to improve the quality of teachers and schools.